UV-Vis Spectroscopic Investigation on Hydrolysis of Starch and Starch-Drug Interaction - GUNASEKARAN, S.; KANCHANA DEVI, M. (Asian Journal of Chemistry, 2010)
Gymnema sylvestre, Pterocarpus marsupium and Madhumeha churnam are the widely prescribed drugs for the treatment of diabetes mellitus by Siddha physicians. In order to estimate the drug activity of each compound, a novel concept namely hydrolysis of starch is applied. Chemically pure, wheat and corn starches are chosen along with human saliva as enzyme. Investigation of hydrolysis of these three kinds of starch by human saliva with and without the addition of antidiabetic drugs has been carried out with the help of UV-Vis technique. Keeping the starch concentration fixed, drug concentration was varied and the variation in absorbance of the starch solution, which is directly proportional to the rate of hydrolysis of starch, has been studied in the range 200-600 nm.